Blunt Renal Trauma in a Pre-Existing Renal Lesion - G.V. Soundra Pandyan; Idris Omo-Adua; Mohammed Al Rashid; Ahmed Bakheet Zaharan (The Scientific World Journal)
A 70-year-old male presented with direct trauma to his loin with gross hematuria, as an isolated case of blunt renal trauma (BRT) due to a traffic accident. A pre-existing renal lesion (PERL) was strongly suspected by his past history of gross macroscopic hematuria and monotrauma to the kidney without other associated injuries. Spiral CT scan with contrast and a retrograde pyelogram (RGP) confirmed an occult complex renal cyst. The gold standard of CT diagnosis in this situation is stressed. Computed tomography is particularly useful in evaluating traumatic injuries to kidneys with pre-existing abnormalities. The decision on the initial course of conservative management, ureteral retrograde stenting to drain extravasation, and its final outcome are discussed. Radical nephroureterectomy was carried out by a transperitoneal approach with an early vascular control of the renal pedicle. A brief review of recent literature has been undertaken.